A importância das cotas para a focalizaç\~ao do Programa Bolsa Família - Ricardo Paes de Barros; Mirela de Carvalho; Samuel Franco; Rosane Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This study has the purpose to evaluate the importance of establishing local quotas for the degree of focus of the Bolsa Família Program. With a focus degree in the order of 57%, the gain of the current system of the beneficiaries? selection on the Bolsa Família Program, when contrasted to a situation where the beneficiaries are selected randomly, is 37 percentage points. When the gain of focus from a municipal system of quotas is around 12 to 14 percentage points, we can conclude that the quota system currently used explains about 1/3 of the total gain of focus achieved in three stages of the current system. Although the central aim of this work is to evaluate the importance of the quotas to the focus of the program, we also investigate the role of the local system of families? registration. The results obtained are, at the very least, interesting. The establishment of quotas corresponds for only a portion of the focus gain of the current selection system used by the program. The high degree of focus achieved by the program currently comes from mainly a successful selection system of the households to be registered.
Keywords: C15; H63; H68; 330